Short-term early exposure to lapatinib confers lifelong protection from mammary tumor development in MMTV-erbB-2 transgenic mice. Issue 1 (December 2017) - Ma, Zhikun; Parris, Amanda; Xiao, Zhengzheng; Howard, Erin; Kosanke, Stanley; Feng, Xiaoshan; Yang, Xiaohe
Abstract Background Although chemopreventative agents targeting the estrogen/estrogen receptor (ER) pathway have been effective for ER+ breast cancers, prevention of hormone receptor-negative breast cancers, such as Her2/erbB-2+ breast cancers, remains a significant issue. Previous studies have demonstrated that administration of EGFR/erbB-2-targeting lapatinib to MMTV-erbB-2 transgenic mice inhibited mammary tumor development. The prevention, however, was achieved by prolonged high dose exposure. The tolerance to high dose/long-term drug administration may hinder its potential in clinical settings. Therefore, we aimed to test a novel, short-term chemopreventative strategy using lapatinib during the premalignant risk window in MMTV-erbB-2 mice. Methods We initially treated cultured cells with lapatinib to explore the anti-proliferative effects of lapatinib in vitro. We used a syngeneic tumor graft model to begin exploring the in vivo anti-tumorigenic effects of lapatinib in MMTV-erbB-2 mice. Then, we tested the efficacy of brief exposure to lapatinib (100 mg/kg/day for 8 weeks), beginning at 16 weeks of age, in the prevention of mammary tumor development in MMTV-erbB-2 mice. Results In the syngeneic tumor transplant model, we determined that lapatinib significantly inhibited tumor cell proliferation. Furthermore, we demonstrated that short-term lapatinib exposure resulted in life-long protective effects, as supported by increased tumor latency in lapatinib-treated mice compared to the control mice. We further established that delayed tumor development in the treated mice was preceded by decreased BrdU nuclear incorporation and inhibited mammary morphogenesis. Molecular analysis indicated that lapatinib inhibited phosphorylation and expression of EGFR, erbB-3, erbB-2, Akt1, and Erk1/2 in premalignant mammary tissues. Also, lapatinib drastically inhibited the phosphorylation and expression of ERα and the transcription of ER target genes in premalignant mammary tissues. We also determined that lapatinib suppressed the stemness of breast cancer cell lines, as evidenced by decreased tumorsphere formation and ALDH+ cell populations. Conclusions Taken together, these data demonstrate that brief treatment with EGFR/erbB-2-targeting agents before the onset of tumors may provide lifelong protection from mammary tumors, through the concurrent inhibition of erbB-2 and ER signaling pathways and consequential reprogramming. Our findings support further clinical testing to explore the benefit of shorter lapatinib exposure in the prevention of erbB-2-mediated carcinogenesis.